(untitled) (Bangladesh Journal of Psychiatry, 2019)
Rapidly onset progressive dementia representing frontotemporal variety had a relentless debilitating impact which sometimes presented with psychological and behavioral symptoms leading to diagnostic dilemma. An adult male had been admitted into the hospital with the complaints of progressively odd and inappropriate social behavior, occasional self-muttering, confusion regarding his surroundings and lack of spontaneous speech for around 9 months. Initially, the patient was diagnosed as schizophrenia comorbid with delirium and treated accordingly. However, no improvement was apparent and the diagnosis was reviewed. Magnetic resonance imaging (MRI) of the brain showed significant cerebral atrophy particularly in the frontal and temporal lobes and finally the case was diagnosed as early onset frontotemporal dementia. The clinician should be cautious about the psychiatric manifestations of frontotemporal dementia to avoid diagnostic error and to manage the patients with more specification from the beginning. Bang J Psychiatry 2019; 33(1): 16-17